Skin damage due to personal protective equipment among health-care professionals in a dedicated COVID-19 hospital of tribal India - Avatarkishan Jaisinghani; Vikas Gupta; Neeraj Gour; Munish Kumar Sharma (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Health-care professionals (HCPs) are at much greater risk of infection due to the exposure to the highly infectious bodily fluids and droplet nuclei and needed use of personal protective equipment (PPE) to reduce the transmission risk. The present study was conducted with an aim of estimating the prevalence of various types of skin injuries among HCPs due to PPE usage. MATERIALS AND METHODS: This descriptive cross-sectional study was conducted after obtaining the institutional ethical approval in a dedicated COVID-19 hospital for a period of 4 months among 276 HCPs wearing grade 2 and 3 PPE kit. The survey questionnaire (Google Forms) was focused on collecting the subject's baseline data (age and gender), duty hours, and type of skin injury experienced due to PPE usage. Chi-square analysis was used to find the association of between dependent and independent variables, and an association was significant for P < 0.05. RESULTS: 51.5% of subjects wore the PPE kit for 5 or more days/week during duty hours and 64.5% of subjects daily wore the PPE kit for 2 or more hours. 81.7% of subjects have suffered from skin injury after PPE usage. The most common symptom/sign for the skin injury that occurred was indentation and pain on the back of the ears (61.5%). CONCLUSION: The frequent skin injuries due to PPE among the HCPs might make them anxious and reduce their morale at work place, so an effective preventive measure should be adopted.